CHARTING THE STAGES OF ENVIRONMENTAL HISTORY : ECOLOGICAL READING OF JAMES MICHENER’S HAWAI’I - Indriyanto, Kristiawan; Darmawan, Ruly Indra; Chandra, Tan Michael (International Journal of Humanity Studies (IJHS), 2023)
This study analyzes James Michener’s Hawai’i to underline how the environment was changed, altered and transformed over time based on differing paradigms of conceptualizing nature and environment. It primarily focuses on how the Native Hawai’ians, American settlers and Chinese immigrants have contrasting ways of perceiving the more-than-human world. The stages of environmental history, as underlined by Worster and Cronon argue how the differing paradigm is intertwined within the cultural contexts and socio-historical circumstances of a particular ethnicity in Hawai’i. Their paradigm manifested through social reproduction resulting from the mode of production, either instrumentalising or respecting the land. Moreover, race, social status and gender also problematize how the environment is conceptualized. From the perspective of environmental history, the environment is positioned as dynamic and changing, contrary to a prior depiction of nature as passive and static. The finding suggests that environmental perspectives in the novel Hawai’i can provide an avenue to reinterpreting human and non-human relationships by considering humanity as part of the natural world.